Total current oscillations in Trichel pulse - Bolotov, O.; Golota, V.; Kadolin, B.; Mankovskyi, S.; Markov, P.; Ostroushko, V.; Pashchenko, I.; Taran, G.; Zavada, L. (Вопросы атомной науки и техники, 2015)
The numerical simulations of negative corona at constant voltage in air are made. Two peaks of total current in Trichel pulse in absence of photoemission appear for very small values of ion-electron emission coefficient. In presence of photoemission the total current oscillations connected with the instability based on photon radiation, photo-emission, and avalanche multiplication take place.